Long-Term, Low Emission and Climate Resilient Development Strategies (LTS) presentation training - day 2 - Chevallier, Romy (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
This presentation was given at the Climate Governance, Diplomacy and Negotiations Leadership Program by Romy Chevallier.